Analisis Strategi Perluasan Usaha Koperasi Kakitangan Petronas Berhad Malaysia - Oktaviani, Christina; Indra Praja, Gunawan; Raudah, Warda; Gunadi, Trida (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Business development of the Koperasi Kakitangan Petronas (Kopetro) requires a careful business strategy to face market changes and dynamic member needs. Cooperatives not only act as providers of financial services, but also as economic platforms for their members to obtain wider benefits through various business opportunities. Therefore, this research aims to analyze how Kopetro implements business expansion strategies and strengthens its position in Malaysian industrial cooperatives. The research method used is descriptive qualitative with a field study approach based on primary data obtained through visits, interviews and other internal document reviews. Based on the analysis, Kopetro has succeeded in expanding the business sector through business diversification, sharia-based financial services, and strengthening information technology, maintaining achievements and recognition as well as managing human resources. This strategy allows Kopetro to adapt to market changes and remain competitive. Kopetro has succeeded in expanding its business to cover various sectors such as trade and retail, tourism and recreation services, catering, property and sharia-based services. However, there are several challenges that can be motivation for Kopetro, such as consolidation of business management, continuous improvement in service quality and international business expansion.